Cuestión social y progresismos en América Latina y África: el pensamiento crítico en la encrucijada - Amor António Monteiro; José Fernando Siquiera da Silva; Raquel Raichelis; Tania Maria Ramos de Godoi Diniz (Eleuthera)
The article discusses the meaning of the social question and its multiple refractions in part of the periphery of capital (Latin America and Africa), as well as analyzes some of the particularities of this social order as unity in diversity, in regions that have historically contributed to the accumulation of capital and stimulated anti-capitalist practices. Based on this, the text analyzes what has more recently been characterized as progressivism, its potentialities and its limits. In the final notes, the scope of progressive and nationalist agendas to promote the eradication of the structural causes that feed social inequality in capitalism, even more so in the context of peripheral and dependent countries, is explored. At the same time, it points out issues that challenge social work in the implementation of a radically anti-capitalist professional ethical-political project in Latin America and Africa.